2011
DOI: 10.1111/j.1600-0404.2010.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Postural responses to low-intensity, short-duration, galvanic vestibular stimulation as a possible differential diagnostic procedure

Abstract: These findings suggest that even weak GVS affects vestibular excitability: cathodal polarization increases whereas anodal GVS decreases excitability. Symmetry and amplitude or velocity of the postural responses, particularly in the eyes closed condition, can differentiate the three groups of subjects tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The peak postural response to GVS was defined as the difference between the peak COP position in the medial-lateral direction during the 5 s GVS stimulus period and the average COP position calculated over the 2 s prestimulus period in this study, which is commonly used to assess the magnitude of postural responses to GVS [ 27 , 28 , 31 ]. It was calculated by subtracting the average value during the prestimulus period from the peak value during the stimulus period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak postural response to GVS was defined as the difference between the peak COP position in the medial-lateral direction during the 5 s GVS stimulus period and the average COP position calculated over the 2 s prestimulus period in this study, which is commonly used to assess the magnitude of postural responses to GVS [ 27 , 28 , 31 ]. It was calculated by subtracting the average value during the prestimulus period from the peak value during the stimulus period.…”
Section: Methodsmentioning
confidence: 99%
“…Balter et al observed that GVS-induced body sway in adult women was significantly greater than that in both gymnasts and untrained adolescents [ 25 ], but the differences in GVS-induced body sway between carsick and healthy subjects were not significant [ 26 ]. Rinalduzzi et al discovered that patients with polyneuropathy had significantly greater postural responses to GVS in comparison with healthy subjects, which suggested that GVS can be useful in detecting people with different vestibular functions [ 27 ]. Tax et al found similar results, reporting that the magnitude of body deviation induced by GVS for patients with bilateral vestibular failure was significantly smaller than that of healthy people, and concluded that GVS is a viable noninvasive method for assessing vestibular function [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the vestibular system can be made also by galvanic vestibular stimulation (GVS), which allows modulation of vestibular nerve firing rate. When applied to an upright subject, bimastoid GVS induces postural sway, according to head position, towards the side of the anodal electrode [ 24 ]. PD subjects as a group produce postural responses to GVS of normal amplitude, latency, and direction of the induced body sway, but when they were subdivided into two subgroups according to a clinical assessment of postural deficit, the more disabled subgroup responded with increased body speed than either controls or the mildly affected patient subgroup.…”
Section: Sensory Organization: Visual Vestibular and Somatosensomentioning
confidence: 99%
“…47 The greater efficiency of L-GVS versus R-GVS in modulating APS probably results from the asymmetry of the cortical vestibular system. 48 Here galvanic inhibition of the left vestibular nerve with excitation of the right vestibular nerve (right-cathodal/leftanodal GVS) results in right vestibular cortex activation, whereas galvanic inhibition of the right vestibular nerve with excitation of the left vestibular nerve (left-cathodal/ right-anodal GVS) 49 activates vestibular cortices bilaterally, at least in healthy participants. 47 Thus, it is conceivable that L-GVS leads to a more widespread cerebral activation in both hemispheres, which could partially compensate for the effects of the typically large brain lesions 28 in patients with left neglect.…”
Section: Vestibular Modulation Of Apsmentioning
confidence: 99%